Periphery, urban environmental quality and perception of residents in medium-sized cities: a case study in the municipality of Itajubá/MG (Research, Society and Development, 2021)
In large metropolises, there are socio-environmental irregularities resulting from urbanization, especially in peripheral regions of urban centers. This reality is reproduced in medium and small cities. This work consists of a case study to understand the issues associated with the peripheral urban environmental quality of a medium-sized city - in this case, the municipality of Itajubá - through a comparison between two neighborhoods with distinct characteristics, but similar under the concept of “periphery”. The evaluation of urban environmental quality was carried out by objective (technical-scientific study of the forms of use and occupation of the soil, free spaces and vegetation cover) and subjective methods (application of questionnaires taking into account the socio-environmental perception of residents and users of neighborhoods). The results obtained allowed the construction of a panorama of urban environmental quality in each of the neighborhoods, which were analyzed pointing out their main differences. A great distinction was noted regarding the socioeconomic conditions among the residents of the two neighborhoods and different perspectives regarding the environment in which they operate. Understanding the different environmental perceptions of people living in the same city is essential for the creation of environmental conservation and preservation programs.